Multi-spectroscopic monitoring of cisplatin-derived species delivery from ureasil polyether hybrid matrix - Molina, Eduardo Ferreira [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Blanchandin, Stephanie; Baudelet, Francois; Briois, Valerie (Taylor & Francis Ltd, 2011)
Driven by the challenges involved in the development of new advanced materials with unusual drug delivery profiles capable of improving the therapeutic and toxicological properties of existing cancer chemotherapy, the one-pot sol-gel synthesis of flexible, transparent and insoluble urea-cross-linked polyether-siloxane hybrids has been recently developed. In this one-pot synthesis, the strong interaction between the antitumor cisplatin (CisPt) molecules and the ureasil-poly(propylene oxide) (PPO) hybrid matrix gives rise to the incorporation and release of an unknown CisPt-derived species, hindering the quantitative determination of the drug release pattern from the conventional UV-Vis absorption technique. In this article, we report the use of an original synchrotron radiation calibration method based on the combination of XAS and UV-Vis for the quantitative determination of the amount of Pt-based molecules released in water. Thanks to the combination of UV-Vis, XAS and Raman techniques, we demonstrated that both the CisPt molecules and the CisPt-derived species are loaded into an ureasil-PPO/ureasil-poly(ethylene oxide) (PEO) hybrid blend matrix. The experimentally determined molar extinction coefficient of the CisPt-derived species loaded into ureasil-PPO hybrid matrix enabled the simultaneous time-resolved monitoring of each Pt species released from this hybrid blend matrix.
Keywords: time resolved X-ray absorption; Raman scattering; UV-Visible absorption; drug delivery